Training of the safe and environment-friendly production house at koro benguk tempeh industry in Mertelu Village, Gedangsari District, Gunung Kidul - Nurul Putrie Utami; Rani Setyawati; Ima Pratiwi (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2022)
Food is a basic need for humans need to live and support health. However, foods are needed to be processed safely, so it can fulfill nutritional needs and also maintain human health. Unsafe food processing can endanger humans because of the increased risk of foodborne disease. In Mertelu, Gedangsari, Gunung Kidul there is a small and medium enterprises (SMEs) that produces koro benguk tempeh. Unfortunately, the application of safe production houses and good processing methods have not been fully implemented in this industry. Thus, this program focused on increasing safe production house training which is one of the requirements for obtaining P-IRT certification. The activity was carried out for two days, 6th and 12th February 2020 with activities such as counseling, training, and mentoring in production houses. This activity was attended by Mertelu’s community who was involved in koro benguk tempeh production. After these programs, they was able to increase understanding of the safe management of production houses. However, some physical facilities were still inadequate to fulfill the standard because the resources limitation. Therefore, they are need further programs to improve existing infrastructure to meet the criteria for a safe food production house as a requirement of Household Food Food Industry (P-IRT) certification